Adoption and Diversity of Agroforestry Systems in the Amazon Biome: A Bibliometric Overview - Pauletto, Daniela; Arco-Verde, Marcelo Francia; Silva, Ivan Crespo; Lopes, Lucas Sérgio de Sousa; Araújo, Anselmo Junior Correa; Lucas, Flávia Cristina Araújo; Santos, Seidel Ferreira dos; Vieira, Thiago Almeida; Dias, Carlos Tadeu dos Santos; Martorano, Lucieta Guerreiro (Land (Basel), 2025)
Agroforestry systems (AFSs) exhibit varied composition and dynamics as intrinsic characteristics of their specificities. In this context, a review of the adoption, composition, and dynamics of AFSs in the Amazon biome was conducted to identify the origin, institutions, and researchers of published studies with results on this scientific topic, focused on trends and characteristics of AFSs diversity in the Amazon. The methodology adopted was a scoping review, based on searches in the Scopus and Web of Science databases, using specific keywords to ensure that the articles addressed topics related to the adoption, composition, and dynamics of AFSs in the Amazon. Following the selection of subtopics, 66 articles were selected and analyzed. The analysis revealed that research on AFSs in the Amazon highlights interactions among traditional knowledge, innovations, and sustainability. The analysis of research published between 1996 and 2023 indicated growth in studies with an interdisciplinary focus, primarily from Brazil. However, internationalization, collaborative networks, and funding factors contribute to the prominence of foreign institutions. Research studies often address topics such as species diversity, agrobiodiversity, and tree growth in agroforestry intercrops. In this context, homegarden agroforestry (HAF) emerges as one of the main subjects of study, encompassing multifunctional environments, richness diversity, and ongoing experimentation with plant species. The choice of species for AFSs is influenced by factors such as labor, personal preferences, and market demands, although loggers and commercial forestry systems tend to have lower diversity, contrasting with HAF. AFSs implementation methods vary according to financing, management, and the farmer’s education and gender. Environmental conservation, food security, ecosystem services, and production flexibility are highlighted as benefits of AFSs, while challenges include technical and economic limitations. This research highlights the strengthening and consolidation of AFSs by addressing scientific gaps and demonstrating the need for studies on the adoption, consolidation, and management of these systems, as well as the relationship between diversity and yield. Future research should be concentrated on deepening studies on the relationship between diversity and yield in AFSs, as well as on management strategies that support the consolidation of these systems in the Amazon biome, integrating innovation, public policy support, and traditional knowledge of farmers.